Ergonomi Ditinjau dari Antropometri pada Interior Restoran Pizza-Hut di Surabaya Timur - Muhammad Solahuddin, Okky Tanudireja (Intra, 2013)
In general of a restaurant, a comfortness of the furniture is very important for the guess,Â  because the more comfortable furniture in a restaurant will make more people want to stay. A restaurant must have furnitures that support guess activity when dining, tables and chairs. For the convenience of feeding activity in living together, required an adjustment of furniture so that an atmosphere of togetherness is more pronounced. Ergonomics is the study of human aspects in the work environment are reviewed in anatomy, psychology, engineering, management and design. Ergonomics and comfort wherever and whoever needed because the effectiveness of a persons performance. A research of ergonomics from the view of anthropometric is a group of ergonomic research of working place measurements with a purpose to get a design of work palce that suit with human dimension. The research method that we used is quantitative analysis descriptive. Quantitative is about describe the furniture and user activity, descriptive is a method that describe the event and situation with a purpose of making a basic data accumulation. Ergonomic from the view of anthropometric of the furniture (dining table and chair, salad bar, waiting chair, lavatory, and cashier register) in Pizza Hut East Surabaya is appropriate with standard just there are little differences. From the result of questionnaire, most of the respondent clarify that they already feel comfort with the furnitures.